2018
DOI: 10.1177/0034355218800802
|View full text |Cite
|
Sign up to set email alerts
|

The Duality of Human Experience: Perspectives From Psychosocial Adaptation to Chronic Illness and Disability—Empirical Observations and Conceptual Issues

Abstract: The historical and conceptual underpinnings of the human experiential duality, within the context of psychosocial adaptation to chronic illnesses and disabilities (CID), were reviewed in our first article on this subject. Included were such topics as dualities inherent in broad psychosocial reactions to CID onset (i.e., coping vs. succumbing, disabled vs. nondisabled identities, experiencing good vs. bad days), models of dualities regarding the concept of denial (i.e., complete vs. partial forms of denial), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 89 publications
(177 reference statements)
0
6
0
Order By: Relevance
“…When using this format, positive developments have been found to correlate negatively with psychological distress (Nordstrand et al, 2017). Negative developments represent posttraumatic deprecation, increased distress and even other kinds of psychopathology, while positive posttraumatic development imply growth (PTG) unlinked to psychopathology and distress (Livneh, McMahon, & Rumrill, 2018). No change, on the other hand, can be indicative of either insufficient traumatic exposure to initiate any posttraumatic development or to resilience (Ozer et al, 2003;Tedeschi & Calhoun, 2004).…”
Section: 派遣至阿富汗的挪威退伍军人中危险和非危险应激源及其与创伤后损伤 或成长的关系mentioning
confidence: 99%
See 1 more Smart Citation
“…When using this format, positive developments have been found to correlate negatively with psychological distress (Nordstrand et al, 2017). Negative developments represent posttraumatic deprecation, increased distress and even other kinds of psychopathology, while positive posttraumatic development imply growth (PTG) unlinked to psychopathology and distress (Livneh, McMahon, & Rumrill, 2018). No change, on the other hand, can be indicative of either insufficient traumatic exposure to initiate any posttraumatic development or to resilience (Ozer et al, 2003;Tedeschi & Calhoun, 2004).…”
Section: 派遣至阿富汗的挪威退伍军人中危险和非危险应激源及其与创伤后损伤 或成长的关系mentioning
confidence: 99%
“…No change, on the other hand, can be indicative of either insufficient traumatic exposure to initiate any posttraumatic development or to resilience (Ozer et al, 2003;Tedeschi & Calhoun, 2004). The assumption is that bi-directional response options reduce the risk of capturing pseudogrowth associated with high levels of distress (Armeli, Gunthert, & Cohen, 2001;Cheng, Wong, & Tsang, 2006;Livneh et al, 2018). This approach may also add to the current understanding of aetiology, diagnostic classification and treatment after trauma (Karanci & Acarturk, 2005;Maguen, Vogt, King, King, & Litz, 2006;Steenkamp, Litz, Hoge, & Marmar, 2015).…”
Section: 派遣至阿富汗的挪威退伍军人中危险和非危险应激源及其与创伤后损伤 或成长的关系mentioning
confidence: 99%
“…In the relational domain, growth typically involves enhanced and deeper relationships, for example, feeling closer to and more appreciative of friends and family, having more trust and compassion toward others. In the existential domain, growth entails a more mature, consoled, and integrated life philosophy or world view; he or she values life more, recognizes its positive aspects, and the personal priorities tend to be more firmly established (Livneh, McMahon, & Rumrill, 2019). Deprecation in these domains are parallel to the negative alterations seen in persons with posttraumatic stress disorder, that is, altered perception of self, altered perception of the relations to others, and altered perception of the world and the meaning of existence (Foa & Rothbaum, 1998; Janoff-Bulman, 2010).…”
mentioning
confidence: 99%
“…For example, Zoellner and Maercker (2006) suggested that different cognitive processes, such as constructive or genuine versus illusory or fake, may be harnessed during different times, and with different magnitudes, throughout the growth process and thus be differentially related to PTG and psychosocial outcomes. A growing number of authors (Frazier et al, 2009; Grace et al, 2015; Jayawickreme & Blackie, 2014; Livneh et al, 2019; Taylor & Armor, 1996; Tennen & Affleck, 2009; Weiss, 2002; Wortman, 2004; Zoellner & Maercker, 2006) posited several competing explanations to the so-called growth reports. Briefly these include (a) active, adaptive coping efforts to manage trauma (e.g., problem solving, cognitive restructuring); (b) self-enhancing, cognitively biased strategies, such as positive (defensive) illusions or perceptions, and various motivational efforts to reaffirm one's self-esteem, perceived well-being, and self-confidence; (c) self-perceptions strategies such as benefit searching and benefit finding, that are mistaken for real, stable growth trajectory; (d) avoidant and denial-type coping modalities that seek to minimize losses incurred; (e) the influence of sociocultural, theological, and philosophical narratives that suffering and personal pain usher in personal growth and transformation; (f) self-presentational maneuvers that seek to convey that one is coping well and experiences positive life changes; (g) several of the longitudinal studies have reported personal growth over time, however, they are based on “average” growth over time, and the data also show individual trajectories that indicate no growth and even decrease in growth over time; (h) people who report personal growth following trauma did so not necessarily because of actual positive changes, but because they downgraded their pretrauma selves (in comparison to their present selves), thus altering the standards by which they assessed their selves and their QOL; (i) growth following adversity is mistaken for the normative change processes of psychosocial adjustment to adversity that include perceived biopsychosocial functioning and community integration; and (j) growth and psychosocial adjustment may be two distinct and independent constructs, and thus reports of perceived growth may not reflect a de facto proof of adjustment (the latter also assessed by a potpourri of independent adjustment measures) following a traumatic experience, but merely a change in life outlook.…”
Section: Growth and Transcendence In Psychology And Human Behaviormentioning
confidence: 99%